Literature Searching in Science, Technology, and Agriculture by Eileen Pritchard and Paula R. Scott. - Mary D. Stoner (Issues in Science and Technology Librarianship, 1997)
This article reviews the book Literature Searching in Science, Technology, and Agriculture. Rev. ed. Westport, CT : Greenwood Press, 1996, by Eileen Pritchard and Paula R. Scott.